2010
DOI: 10.1097/inf.0b013e3181e8b346
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Characterization of Norovirus Compared With Rotavirus Acute Diarrhea Episodes in Chilean Children

Abstract: Noroviruses are a significant cause of moderate to severe endemic ADE in Chilean children. Although significantly less severe than rotavirus as a group, most norovirus episodes were moderate to severe clinically. An effective norovirus vaccine would be of significant additional benefit to the current rotavirus vaccine in decreasing disease burden associated with ADE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
15
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
6
15
1
4
Order By: Relevance
“…Comparisons of the average severity scores categorized by different virus infections showed a statistical significant difference only between the group with RV infection alone versus the group with unidentifiable viruses, suggesting that children infected with RV alone likely experience more severe clinical symptoms [Colomba et al, 2006;O'Ryan et al, 2009;O'Ryan et al, 2010]. It is interesting that 99.5% of the pediatric diarrhea patients enrolled in this study were under 2 years of age although we aimed for <5 years, consistent with the findings from other studies in China [Qiao et al, 1999;Fang et al, 2005].…”
Section: Discussionsupporting
confidence: 85%
“…Comparisons of the average severity scores categorized by different virus infections showed a statistical significant difference only between the group with RV infection alone versus the group with unidentifiable viruses, suggesting that children infected with RV alone likely experience more severe clinical symptoms [Colomba et al, 2006;O'Ryan et al, 2009;O'Ryan et al, 2010]. It is interesting that 99.5% of the pediatric diarrhea patients enrolled in this study were under 2 years of age although we aimed for <5 years, consistent with the findings from other studies in China [Qiao et al, 1999;Fang et al, 2005].…”
Section: Discussionsupporting
confidence: 85%
“…This is due to norovirus causing less severe diarrhoea than rotavirus and parents tend not to seek medical services [25,26]. In our study, the severity of diarrhoea episodes was similar in children with and without NoV and similar high detection rates had been reported from Chile, India and Nicaragua at that time when the vaccines had not been introduced [18][19][20].…”
Section: Discussionsupporting
confidence: 68%
“…Globally, hospital-based series in children with diarrhoea report a median of 14%, which seems lower than the proportions detected in our study [17]. Although our data suggests an annual increase in the proportion of cases, similar detection rates had been reported from Chile, India and Nicaragua prior to rotavirus vaccine introduction [18][19][20]. This relative increase may also be due to the decrease of number of rotavirus-related hospitalizations [10,11] and all-cause diarrhoea cases due to the effectiveness of the rotavirus vaccine [21] and the herd effect of the vaccine that has resulted in an overall and not a real increase in the overall number of NoV cases.…”
Section: Discussioncontrasting
confidence: 51%
“…3 It was suggested that children in the developing countries can exhibit higher prevalence of antibodies directed against NoV as compared to developed countries due to early exposure, even though inconsistently. Previous studies indicated that infection with enteric viruses including NoV is significantly associated with early age [46][47][48] and consequently early exposure leads to development of immunity against the virus. In a recent longitudinal study held in the Cameroon, 49 reports show that adults and children show similar rates of infections with the virus.…”
Section: Viral Shedding Natural Infection With Nov and Seroprotectionmentioning
confidence: 99%